The Effect Of Socialization, Taxpayer Awareness And Tax Morale On Taxpayer Compliance (Study On Smes Benai District Kuantan Singingi Regency) - Kumala Dewi, Dessy (CV. Inara, 2022)
The purpose of this study is to analyze the effect of socialization, taxpayer awareness and tax morale on taxpayer compliance. This research is an empirical study conducted on SMEs in Benai District Kuantan Singingi Regency. This research design includes qualitative research. The population and sample in this study were SMEs in Benai District, Kuantan Singingi Regency. Sampling was done through proportional random sampling. Data obtained through the distribution of questionnaires. Data analysis regarding multiple linear regression and independent sample t test with the help of SPSS software version 21. The results showed that: 1). socialization has no effect on taxpayer compliance, 2). taxpayer awareness has no effect on taxpayer compliance, and 3). tax morale has a significant effect on taxpayer compliance.